THE EFFECT OF THE USE OF PROBLEM BASED LEARNING (PBL) MODEL ON THE RESULTS OF STUDENTS LEARNING SCIENCE IN SMP - Merlinda Kurnia Mamu; Adrianus Nasar; Ilyas Ilyas (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
The purpose of this study is to determine the effect of the use of the problem-based learning (PBL) learning model on science learning outcomes of students of SMP Negeri 2 Ruteng Beokina in the academic year 2019/2020. In this study, researchers used a type of survey research with a quantitative approach. The design of this study is ex-post facto. The population in this study were all eighth-grade students of SMP Negeri 2 Ruteng Beokina, with 178 students. The sample in this study amounted to 66 people. The sampling technique uses simple random sampling. Data obtained from the study sample in the form of science learning outcomes value of pressure material. Data analysis using t-test. The results of the study indicate that learning physics using PBL learning models can affect the learning outcomes of science students of SMP Negeri 2 Ruteng Beokina in the academic year 2019/2020. This is evidenced by the results of calculations using SPSS software version 24, namely the value t = 19.095, of sig (2-tailed) or (0,000 <0.05) at α = 5% and dk = 65.